IMPLEMENTATION OF RELIGIOUS MODERATION IN MEDAN CITY GOVERNMENT POLICIES: The Perspective of the Interfaith Harmony Forum (FKUB): IMPLEMENTASI MODERASI BERAGAMA DALAM KEBIJAKAN PEMERINTAH KOTA MEDAN: Perspektif Forum Kerukunan Umat Beragama (FKUB) - Khairani, Vira; Fitriani; Lubis, Muhammad Nassar; Febrianti, Lidya (Jurnal Studi Islam dan Sosial, 2026)
Indonesia faces the challenge of dynamic diversity, where religious moderation is a national priority for maintaining social harmony, but its implementation at the regional level often faces bureaucratic obstacles and gaps in understanding. This study aims to analyze the implementation of religious moderation policies by the Medan City Government from the perspective of the Forum for Religious Harmony (FKUB) as a strategic partner of the government. The method used is library research with a descriptive qualitative approach, relying on primary data in the form of Medan Mayor Regulation No. 28 of 2021 and the 2025 internal reference book of the FKUB of Medan City, supported by relevant secondary literature. The results of the study show that the Medan City Government has a fairly strong regulatory foundation, but from the FKUB's perspective, optimization is still needed in terms of operational budget support and more massive socialization down to the sub-district level to prevent conflicts over the establishment of houses of worship. In conclusion, the synergy between city government regulations and the mediating role of religious leaders in the FKUB is the key to the success of religious moderation in Medan City, thus requiring the strengthening of more intensive institutional dialogue. This study contributes to the scientific discourse by formulating a conflict resolution model that integrates 'Anak Medan' local wisdom and the 'Dalihan Na Tolu' philosophy into formal policy structures, providing a strategic alternative for strengthening religious moderation in heterogeneous urban areas.